On the existence of equations of evolution - J. Lubliner (International Journal of Mathematics and Mathematical Sciences)
A time-independent, non-autonomous non-linear system governed by a principle of determinism (the state at a given time is determined by the initial state and by the control history during the intervening closed interval) is shown to obey a generalized evolution equation (1.2), where n is such that the state is continuously differentiabie with respect to time whenever the control is of class Cn.